Crystal structure of 1,10-phenanthrolinium bromide dihydrate, C12H9N2Br - Adeloye Adewale O.; Clayton Hadley S. (Zeitschrift für Kristallographie - New Crystal Structures)
C12H9N2Br, triclinic, P1‾$\overline{1}$ (no. 2), a = 7.4005(13) Å, b = 9.4122(16) Å, c = 9.7916(17) Å, α = 98.235(9)°, β = 101.744(8)°, γ = 111.005(7)°, V = 605.69(18) Å3, Z = 2, Rgt(F) = 0.0209, wRref(F2) = 0.0514, T = 100(2) K.